We are not Gametes: Distinguishing between Abortion and Contraception. Issue 3 (1st September 2016) - Saad, Toni
Abstract : It is sometimes argued that interruptions of the life's continuum which have the same end result are morally equivalent. In other words, abortion and contraception are ethically identical because both prevent birth and the development of persons. We will examine two major arguments in favour of this thesis: (1) all things that are potential persons have equal moral status. Hence preventing fertilisation of gametes is morally identical to destroying an embryo; (2) all interruptions of the continuous process which leads to the creation of a person are morally equivalent; abortion and contraception are morally indistinguishable. These arguments challenge those who distinguish between abortion and contraception. It is argued, however, that there is good reason to doubt their validity. Furthermore, an argument is offered which confirms the ethical boundary between abortion and contraception on the basis that an embryo is something greater and other than the sum of its constituent gametes.